Model Pembelajaran Project Based Learning (PJBL) Berbantuan RPG Maker MV terhadap Kemampuan Berpikir Kreatif Siswa - Z, M Sulistio; Sumardi, Hari; Susanta, Agus (Jurnal Pendidikan Matematika : Judika Education, 2025)
The purpose of this study was to determine whether the effect of the Project Based Learning (PJBL) learning model on the creative thinking ability of class X SMKS 10 Telkom students on the material of arithmetic and geometric rows and series. The method used in this research is quantitative and descriptively analysed using the quasi experimental design research method. The study population consisted of all students in class X TJA SMKS 10 Telkom Bengkulu City, with 10 students in class X TJA B as the experimental class and 10 students in class X TJA A as the control class. Homogeneity, normality, and hypothesis tests were used to analyse the data for testing the results of this study. We used SPSS 25.0. The results showed that Asymp. Sig (2-tailed) of 0.001 < 0.05 so that H0 is rejected and H1 is accepted, thus indicating that the Project Based Learning learning model assisted by RPG Maker MV affects students' creative thinking skills on the material of arithmetic and geometric rows and series. Keywords: Creative Thinking Skills, Project Based Learning, RPG Maker MV